Faktor-Faktor Yang Mempengaruhi Nilai Perusahaan - Nariman, Augustpaosa; Ekadjaja, Margarita (Manajemen Bisnis Kompetensi, 2019)
Increasing the wealth of shareholders is one of the purpose of financial management. Shareholders wealth can be seen from the increase of corporate value. Several issue related to corporate governance factor becoming popular topic since the economic crisis in Indonesia. According to the corporate governance factor is a system to control corporate, the mechanism corporate governance are management shareholding, institutional shareholding, government shareholding, board size, board independence. Corporate governance factor for this research are institutional shareholding, board size, and board independence The aim of this research are to understanding and analyzing the effect of corporate governance factor consists of institutional shareholding, board size, and board independence to value of the firm. The populations in this research were manufacturing companies listed in IDX (Indonesia Stock Exchange) within period 2013-2016. The method of sampling in this research used the purposive sampling method. The results showed that corporate governance factor consists of institutional shareholding, board size, and board independence had effect on value of the firm of manufacturing companies list on the Indonesia Stock Exchange.Keywords: corporate governance, institutional shareholding, board size, board independence, value of the firm